Ho Chi Minh City adaptation to climate change : (Asian Development Bank (ADB), 2010)
Ho Chi Minh City (HCMC) ranks among the top 10 cities in the world with populations most likely to be severely affected by climate change. By 2050, millions of its citizens will be at increased risk from regular and extreme climatic events such as floods, droughts, and tropical storms. To help reduce the impacts of these risks, this study provides HCMC's government and private sector with projections of HCMC's 2050 exposure in key sectors and areas, and proposes structural and nonstructural measures to build climate resilience in the city's most vulnerable sectors and areas.